CMV AND EBV CO-INFECTIONS IN ACTIVE PULMONARY TUBERCULOSIS (Universal International Scientific Journal, 2026)
Active pulmonary tuberculosis (APT) is a major global health challenge, and viral infections exacerbate the disease. In particular, herpesviruses such as Cytomegalovirus (CMV) and Epstein–Barr virus (EBV) can interact with the immune system and influence the development of TB disease. This review analyzes the relationship between CMV/EBV and TB, based on the available scientific literature, and sheds light on their immunological mechanisms and impact on clinical outcomes.
Keywords: APT; CMV; EBV